Efficacy and safety of Chondroxide ointment in combine therapy of osteoarthritis patients - I. V. Kudrjavtzeva; N N Chizhov; N M Braginskaya; A. A. Dolgaleva; I A Istranen (Научно-практическая ревматология)
Objective. To assess the efficace and safety of Chondroxide ointment in OA pts. Methods. 27 OA pts were included in clinical investigation. All the pts used Chondroxide preparation as a topical application. Results. Considerable and marced improvement were achieved in 18 OA pts (66,6%). In 9 cases the efficacy of treatment was abcent. Conclusion. Chondroxide ointment is highly effective and safe preparation in OA pts treatment